Quantification of propionic acid from Scutellaria baicalensis roots - Eunjung Son; Ho Kyoung Kim; Hyun Sik Kim; Mee Ree Kim; Dong-Seon Kim (Integrative Medicine Research)
Background: Propionic acid is a widely used preservative and has been mainly formed by artificial synthesis or fermentation. In the case of natural products, the presence of propionic acid is viewed as a sign that an additive has been introduced for antimicrobial effects. Methods: In this work, the propionic acid that occurs in Scutellaria baicalensis roots was studied. A quantification method was developed, validated, and showed good linearity, low limit of detection, and limit of quantification values, as well as fine precision and recovery rate. The developed method was applied to the analysis of S. baicalensis roots collected in South Korea and China. Results: The detection rate for all samples was 94.0%. The average concentration was 0.41 ± 0.24 mg/g from the China sample and 0.76 ± 0.28 mg/g from the Korea sample. Conclusion: This study is the first to report that propionic acid exists in S. baicalensis roots and also provides a useful ultra performance liquid chromatography analysis method for its quantification.